A sociological journey into space: architecture and social structure in a changing local government organisation - Hirst, Alison (2011)
The relationship between the physical work environment and the social practices associated with it has until recently been neglected in studies of organisation and public management. Although there is now growing interest in organisational space, the area is characterised by competing definitions and fragmented contributions. There are still relatively few empirical studies, and no ethnographic studies which have analysed the relationship between organisational space and organisational social processes over time and in depth. A sociological analysis of the interrelationship between the material environment of an organisation and organisational social structures and processes is undertaken, using a case study of a UK local authority which undertook a spatial reconfiguration of all its staff over a period of four years. During this time, successive groups of staff were moved into new or refurbished buildings which were designed to support 'new ways of working', a term which stood for fluid networking across structural boundaries, in particular, directorates and hierarchical levels. In these new offices, all staff were based in open plan space and no employees had official 'ownership' of a particular desk. The new spatial configuration grouped 'strategic' managers in a central headquarters building, 'back office' employees in an adjacent building, and relocated 'locality' staff in 'Public Service Villages' which integrated staff across directorates. Senior managers expressed ambitious intentions for the way in which this new configuration could reshape what they presented as an outdated bureaucracy into an outward-looking, inspirational organisation based on a networked form. The study focuses chiefly on the strategic centre and back office buildings and compares officially stated intentions with the social processes and structures that actually emerged over time in both buildings. The case study is ethnographically-oriented and works within Pragmatist criteria of truth and validity. The analysis uses Lefebvre's conceptualisation of the social production of space to integrate social and spatial dimensions, and link the configuration of space with the social structures of capitalism. To compensate for Lefebvre's relative neglect of agency in the production of space, use is made of Berger and Luckmann's analysis of the social construction of reality. Thus, the thesis applies what Harvey terms the 'geographical imagination', which relates everyday spatial processes to the wider sociospatial configuration ofthe society of which they are a part. The first two contributions link the spatial structure of organisation with the degree of autonomy given to employees. In the strategic centre, new networked structures emerged to an extent, but the transformation to a network form was limited by a hierarchical sociospatial structure, which the study conceptualises as the 'invisible office'. In the back office building, the official priorities appeared to have shifted towards the cost-efficient use of space and the capacity to flex the organisation structure rapidly. This resulted in a sociospatial structure in which the key distinctions were between the top managers and all other staff, and between employees who established unofficial ownership over particular desks and those who could not. In this building, the use of space mapped closely onto the non-inclusive roles which Kallinikos argues are the basic units from which modern organisation is composed. The exchangeable use of space can therefore be understood as a shift in which the efficiency and rationality of bureaucratic organisation is increased. In both buildings, the group of employees at the top of the organisational hierarchy (in what was officially suggested should be an entirely non-hierarchical environment) maintained a semi-private space. While both office environments had the same material capacity for exchangeability, the more powerful organisational members appeared to take root and from this position of spatial stability planned the flexible reconfiguration of other employees.